A Review on Novel Therapeutic Modalities and Evidence-based Drug Treatments against Allergic Rhinitis - Kumar, Bhupendra; Deshmukh, Rohitas (Current Pharmaceutical Design, 2024)
Allergic rhinitis (AR) is an IgE-mediated atopic disease that occurs due to inhaled antigens in the immediate phase. Misdiagnosis, insufficient treatment, or no treatment at all are frequent problems associated with the widespread condition known as chronic allergic rhinitis. AR symptoms include runny, itchy, stuffy, and sneezing noses. Asthma and nasal polyps, for example, sometimes occur simultaneously in patients. In order for people living with AR to be as comfortable and productive as possible, treatment should center on reducing their symptoms. The online sources and literature, such as Pubmed, ScienceDirect, and Medline, were reviewed to gather information regarding therapeutic modalities of AR and evidence-based treatments for the disease as the objectives of the present study. An increasing number of people are suffering from AR, resulting in a heavy financial and medical burden on healthcare systems around the world. Undertreating AR frequently results in a decline in quality of life. Treatment compliance is a critical challenge in the administration of AR. Innovative therapies are needed for RA to provide patients with symptom alleviation that is less expensive, more effective, and longer duration of action. Evidence-based guidelines are helpful for managing AR illness. Treating AR according to evidence-based standards can help in disease management. AR treatment includes allergen avoidance, drug therapy, immunotherapy, patient education, and follow-up. However, AR treatment with intranasal corticosteroids is more popular. Hence, in this review article, treatment options for AR are discussed in depth. We also discussed the incidence, causes, and new treatments for this clinical condition.
Keywords: corticosteroids